A Study on Political Reform and Ethical Improvement - Kim Taek (International Journal of Advanced Culture Technology(IJACT), 2023)
Through this incident, it reminds me of the idea that personnel appointments are everything once again. Public officials should try to be good at ethics and conduct. If a public official fails to fulfill his or her role as a public official, how can the public trust him or her? You should know that the country does not exist under that official. Looking back on the constitutional history after liberation, it is undeniable that the collusion between politicians and businessmen shocked the people with many suspicions and distrust, and the various irregularities they caused disrupted healthy democracy and the national economic order. In this respect, this paper focuses on Korean political reform measures, but also examines ways to improve public officials' ethics. This paper focuses on that political reform should move in the direction of revitalizing the function of the National Assembly and allowing autonomous and independent parliamentary activities. Parliamentary activities should not be too dampened, and it should not end in a brief promotion in consideration of election votes. The ruling and opposition parties should seriously consider and implement this political reform plan. As one of the people, I hope that this privilege reform plan can be a touchstone for the advancement of political culture. This paper was studied as follows. First, the purpose and justification of political reform were identified. Second, it emphasized the need to improve public service ethics. Third, the problems and improvement measures of political reform were considered.